2017
DOI: 10.1039/c7sc02986a
|View full text |Cite
|
Sign up to set email alerts
|

A β-Carbon elimination strategy for convenient in situ access to cyclopentadienyl metal complexes

Abstract: Stable pre-ligands and common metal salts provide, via β-carbon elimination, access to Cp-metal complexes suitable for in situ catalyst preparation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
23
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(24 citation statements)
references
References 78 publications
1
23
0
Order By: Relevance
“…Rovis reported that the use of a η 5 ‐heptamethylindenyl‐rhodium(III) [Ind*Rh III ] complex, which is synthesized by anion exchange (Scheme , middle and bottom), improves diastereoselectivity of the [4+2] annulation of benzamides with 3,3‐disubstituted cyclopropenes . Cramer reported the synthesis of unsubstituted indenyl‐ and 1,2,3‐trimethylindenyl–rhodium(III) complexes by β‐carbon elimination (Scheme , bottom), but their catalytic activity toward the C−H bond functionalization was not demonstrated . Thus, structural diversity of IndRh III complexes is very limited, especially, an electronically tuned one has not been reported to date.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Rovis reported that the use of a η 5 ‐heptamethylindenyl‐rhodium(III) [Ind*Rh III ] complex, which is synthesized by anion exchange (Scheme , middle and bottom), improves diastereoselectivity of the [4+2] annulation of benzamides with 3,3‐disubstituted cyclopropenes . Cramer reported the synthesis of unsubstituted indenyl‐ and 1,2,3‐trimethylindenyl–rhodium(III) complexes by β‐carbon elimination (Scheme , bottom), but their catalytic activity toward the C−H bond functionalization was not demonstrated . Thus, structural diversity of IndRh III complexes is very limited, especially, an electronically tuned one has not been reported to date.…”
Section: Methodsmentioning
confidence: 99%
“…[5] In the CÀHb ond functionalization, only as ingle example of the indenyl-rhodium(III) complex-catalyzed reaction has been reported. [8] Thus, structural diversity of IndRh III complexes is very limited,e specially,a ne lectronically tuned one has not been reported to date. [6,7] Cramer reported the synthesis of unsubstituted indenyl-and 1,2,3-trimethylindenyl-rhodium(III) com-plexes by b-carbone limination (Scheme 1, bottom), but their catalytic activity toward the CÀHb ond functionalization was not demonstrated.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, reported examples of β‐carbon elimination reactions of alkoxides to give well‐defined metal complexes are still rare. To the best of our knowledge, there are only a few reports on isolation of metal complexes derived from β‐carbon elimination of tertiary alkoxide complexes, [8b, 14] only one report on isolation of metal complexes derived from β‐carbon elimination of secondary alkoxide complexes (i.e., the reactions of C 5 Me 5 C(OH)H(R) (R=Ph, n ‐pentyl and CO 2 Et) with [Rh(COD)(OH)] 2 to give ( η 5 ‐C 5 Me 5 )Rh(COD)), and no reports on isolation of metal complexes derived from β‐carbon elimination of primary alkoxide complexes.…”
Section: Methodsmentioning
confidence: 99%
“…The released hydrochloric acid during the complexation is incompatible with some sensitive functional groups of designer Cp scaffolds. We have developed a complementary complexation strategy capitalizing on β-carbon elimination of cyclopentadienyl carbinols as Cp-ligand precursors 9. While this method consists of an improvement, it requires the synthesis of the ligand precursor by an additional synthetic step.…”
Section: Introductionmentioning
confidence: 99%